Assessment of DNA Damage by RAPD in Paracentrotus lividus Embryos Exposed to Amniotic Fluid from Residents Living Close to Waste Landfill Sites. (11th July 2010) - Guida, Maurizio; Guida, Marco; De Felice, Bruna; Santafede, Daniela; D'Alessandro, Raffaella; Di Spiezio Sardo, Attilio; Scognamiglio, Marianna; Ferrara, Cinzia; Bifulco, Giuseppe; Nappi, Carmine
Abstract : The aim of this study was to assess the genotoxic effects of environmental chemicals on residents living near landfills. The study was based on samples of amniotic fluid from women living in the intensely polluted areas around the Campania region of Italy compared to a nonexposed control group. We evaluated the genetic effects that this amniotic fluids collected in contaminated sites had on Paracentrotus lividus embryos. DNA damage was detected through changes in RAPD (Random Amplified Polymorphism DNA) profiles. The absence of the amplified DNA fragments indicated deletions in Paracentrotus lividus DNA exposed to the contaminated amniotic fluids when compared to equal exposure to uncontaminated fluids. These results show the ability of RAPD-PCR to detect and isolate DNA sequences representing genetic alterations induced in P. lividus embryos. Using this method, we identified two candidate target regions for DNA alterations in the genome of P. lividus . Our research indicates that RAPD-PCR in P. lividus embryo DNA can provide a molecular approach for studying DNA damage from pollutants that can impact human health. To our knowledge, this is the first time that assessment of DNA damage in P. lividus embryos has been tested using the RAPD strategy after exposure to amniotic fluid from residents near waste landfill sites.